Functional and structural changes of the photosystem II complex induced by high irradiance in cyanobacterial cells - Komenda, J; Masojídek, J (European journal of biochemistry, 1995)
A gradual disintegration of the photosystem II (PSII) complex, initiated by a release of the chlorophyll-protein CP43, was identified during low-temperature illumination of Synechococcus cells. This process was slower compared to the decline of the PSII primary charge separation activity, and much slower than the photoinactivation of oxygen evolution. All three processes were slowed down in the presence of diuron. The results indicate that when the PSII repair was blocked, the inactivation of charge separation activity and the release of CP43 preceded the degradation of the D1 protein. In contrast, a much faster degradation of D1 connected to its rapid exchange was triggered by inactivation of oxygen evolution, and no disassembly of PSII was needed. We propose the existence of two different mechanisms of D1 degradation in the cells of the thermophilic cyanobacterium Synechococcus elongatus.
Keywords: Photosystem II Protein Complex; Cyanobacteria; Photosynthetic Reaction Center Complex Proteins; světlosběrné proteinové komplexy; fotosyntetická reakční centra (proteinové komplexy); Light-Harvesting Protein Complexes; fotosystém II (proteinový komplex); sinice